The Impact of Facebook Social Media Usage on the Social Relationships of Teenagers in Makassar City - Hidayat, Rahmatul; Erniwati, Erniwati; Ismail, Ismail (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to investigate the influence of Facebook social media on the social relationships of teenagers in Makassar City, along with the government's endeavors to mitigate the adverse effects of Facebook usage in this demographic. Employing a qualitative approach, the research utilizes various data collection methods, including in-depth interviews with teenagers aged 18-22, discussions with the City's Communication and Information Office (Diskominfo), observation of teenage Facebook users, and document analysis related to the study's focus. The research findings undergo thorough analysis through stages of data reduction, presentation, and conclusion drawing. The results reveal that Facebook usage has both positive and negative impacts on teenagers in Makassar City. Positively, the platform facilitates the establishment and regulation of friendships, promoting positive communication through content sharing and constructive comments. Conversely, negative consequences arise as users feel offended by statuses, comments, and uploaded media touching on personal matters. Moreover, these negative impacts extend to teenagers displaying apathy towards social relationships, leading to procrastination and forgetfulness. Teenagers in Makassar predominantly use Facebook for gaming, entertainment, watching, and online selling. The government, as a key policymaker, encounters challenges in significantly minimizing the negative effects of Facebook usage among teenagers due to privacy concerns. Current governmental initiatives are confined to socialization campaigns and encouraging responsible and positive social media use among teenagers. Despite these efforts, more attention is required to effectively address the identified negative impacts.